Socialização da informação no processo de ensino-aprendizagem: uma análise a partir da teoria da sociedade habermasiana - Brandão, Alini Casimiro (2014)
In the configuration of contemporary society, information emerges as a phenomenon essential to the construction of knowledge, interactive communication and mutual understanding between individuals, peoples, cultures and nations. From this perspective, Information Science resize your needs pragmatic approaches, especially the technical assumptions for transfer socializing information. It is in this perspective, therefore, this research seeks to understand, the Theory of Communicative Action (TAC) as teachers of Graduate Programs in Information Science from Northeast conceive the concept and dynamics of information in the process of teaching and learning. Of descriptive and qualitative nature, uses mixed questionnaire, developed in Google Docs and sent by e-mail, as an instrument for data collection and categorization technique, in this content analysis to analyze these. Thus, it is understood that the concepts of correlation and dynamic information of the orientation of instrumental rationality, conceived the idea of the Information Transfer, predominates over communicative rationality, organizer of Socialization Information. From this perspective, the research concluded that the practices of teaching and learning of Graduate Programs in Information Science, information transfer (instrumental rationality) has been losing ground to the assumptions of socialization of information (communicative rationality), establishing, albeit incipient strike a balance.